Deaths in traffic accidents associated with THC abuse - Monika, Másilková; Radek, Kolčava; Miroslav, Bosák; Jitka, Otásková Tamáš (Soudni lekarstvi, 2020)
From the National Registry of autopsies and toxicology examinations, we selected the deceased for 2015, 2016, 2017 and January 2018 active road accident participants, i.e. pedestrians, cyclists and motor vehicle drivers. From these, we further selected those who were tested for THC presence. Of the 836 deceased active road accident participants, only 251 (i.e. 30%) were tested for cannabinoids, most often passenger car drivers, 46 percent. Of the 251 people tested, THC was demonstrated in 12 (4.8%), most commonly motorcycle drivers (7.8%) and passenger car drivers (3.4%). Of the 12 positive people, 7 were found to have a possible effect of THC ingestion on the road accident, but only one participant was found to have overdosed on THC, and 2 were reported by the dissecting physician to have had no effect on the accident. In the Czech Republic, when driving under the influence of addictive substances, there is no uniform procedure for qualification, whether it is an offence or an offence, and thus in the award of punishment. While somewhere there is an effort to divide this wrongdoing into offences and crimes, elsewhere it practically always only constitutes an offense. This situation seeks to resolve the instruction of the Attorney-at-chief 1 SL 732/2018 of 29 December 4.2019, which, however, arose without any discussion with the professional public, which is heavily criticized especially for the absurly high limits, which in particular in morphine and cocaine are practically unachievable. At the time of this writing, the impact of this guideline on practice is not clear.
Keywords: Automobile Driving; Motorcycles; Accidents, Traffic; řízení motorových vozidel; effect of THC on drivers; tetrahydrokanabinol; motocykly; THC; Humans; Dronabinol; traffic accident; dopravní nehody; Czech Republic; National Registry of autopsies and toxicology examinations; lidé; penalties in traffic; Česká republika